Green Hydrogen - How to set up a class for students with deafness - Piropo, Wellington Marcelino; Rodrigues, Aline Varella; Cursino, Ana Cristina Trindade (Seven Editora, 2024)
This chapter of the book emphasizes the importance of making chemistry content accessible to deaf students. Using hydrogen as a thematic support, the research carried out as an applied methodology aimed to identify the options for adapting a class to meet the needs of deaf students. Given the lack of adaptation in many classes for this audience, the study proposed the application of the methodology of investigative experimentation, with the principles of the Three Pedagogical Moments. DOI:https://doi.org/10.56238/sevened2024.015-002